Rationale and design of the SERVE‐HF study: treatment of sleep‐disordered breathing with predominant central sleep apnoea with adaptive servo‐ventilation in patients with chronic heart failure. (August 2013) - Cowie, Martin R.; Woehrle, Holger; Wegscheider, Karl; Angermann, Christiane; d'Ortho, Marie‐Pia; Erdmann, Erland; Levy, Patrick; Simonds, Anita; Somers, Virend K.; Zannad, Faiez; Teschler, Helmut
<x xml:space="preserve">Abstract</x> Aims Central sleep apnoea/Cheyne–Stokes respiration (CSA/CSR) is a risk factor for increased mortality and morbidity in heart failure (HF). Adaptive servo‐ventilation (ASV) is a non‐invasive ventilation modality for the treatment of CSA/CSR in patients with HF. Methods SERVE‐HF is a multinational, multicentre, randomized, parallel trial designed to assess the effects of addition of ASV (PaceWave™, AutoSet CS™; ResMed) to optimal medical management compared with medical management alone (control group) in patients with symptomatic chronic HF, LVEF ≤45%, and predominant CSA. The trial is based on an event‐driven group sequential design, and the final analysis will be performed when 651 events have been observed or the study is terminated at one of the two interim analyses. The aim is to randomize ∼1200 patients to be followed for a minimum of 2 years. Patients are to stay in the trial up to study termination. The first patient was randomized in February 2008 and the study is expected to end mid 2015. The primary combined endpoint is the time to first event of all‐cause death, unplanned hospitalization (or unplanned prolongation of a planned hospitalization) for worsening (chronic) HF, cardiac transplantation, resuscitation of sudden cardiac arrest, or appropriate life‐saving shock for ventricular fibrillation or fast ventricular tachycardia in implantable cardioverter defibrillator patients. Perspectives The SERVE‐HF study is a randomized study that will provide important data on the effect of treatment with ASV on morbidity and mortality, as well as the cost‐effectiveness of this therapy, in patients with chronic HF and predominantly CSA/CSR. Trial registration ISRCTN19572887